Gender differences in adult numeracy skills: what is the role of education?. Issue 6 (3rd October 2018) - Cook, Rose
ABSTRACT: Previous research suggests that as societies empower women educationally, gender differences in numeracy skills will decline. Using direct measures of 56, 142 adults' numeracy skills from the Programme for International Assessment for Adult Competencies (PIAAC), this article studies whether this claim is evidenced across 20 Organisation for Economic Co-operation and Development (OECD) countries. Results show that in many countries, as education has equalised over generations, gender differences in adult numeracy skills have indeed declined. However, women's advances in education have not always been matched by a reduction in the gender difference in adult numeracy. Contrary to expectations, gender differences in fields of study in further and higher education cannot systematically explain gender differences in adult numeracy. This suggests that to achieve gender equality in numeracy skills, societies must do more than empower women educationally. More research is needed on the educational policies, contextual, and life course factors contributing to gender differences in adult numeracy in post-industrial societies.